SYSTEM ANALYSIS AND DESIGN OF THE GAME «SHOOTING SIMULATION IN A SHOOTING RANGE» - D. Yanchev; O. Sakaliuk; D. Popkov (Автоматизация технологических и бизнес-процессов)
The article examines the system analysis and design of the game «Shooting Simulation in a Shooting Range», which is a relevant area in the context of the modern gaming industry’s development. The research emphasizes the importance of using information technologies to create interactive products that combine high levels of graphic detail, realistic physical models, and user-friendly interfaces. The main purpose of the study is to develop software for a shooting simulation using modern tools and methods. The research identifies the key system requirements, describes the stages of project implementation, and proposes approaches to solving the main technical challenges.